21. Adverse Childhood Experience among Adolescents in the Ethnic Minorities of Lang Son Province - Vinh, Ngo Anh; Hoan, Nguyen Thi Mai (Tạp chí Nghiên cứu Y học, 2024)
The objective of this paper was to investigate the prevalence of adverse childhood experiences (ACEs) and associated factors among adolescents of the ethnic minorities of Lang Son province. This cross-sectional research was carried out in Lang Son province. A total of 845 students in boarding schools participated in the study. Adverse Childhood Experiences Questionnaire (ACE-Q) was used to measure ACEs. Multivariate Logistic Regression was performed to identify associated factors with ACEs. Emotional abuse is the most common ACE, experienced by 21.9% of the participants, followed by emotional neglect at 14.4% and parental divorce at 11%. Overall, 48.7% experienced ACEs in their lifetime. The frequency of parental visits every two months significantly increases the likelihood of adverse experiences (OR = 2.41, 95% CI: 1.43-4.05, p-value = 0.0009), and living in households with fewer than ten people versus ten or more significantly decreases the risk (OR = 0.48, 95% CI: 0.33-0.70, p-value < 0.0001). Additionally, internet use for 4 hours/day (OR = 0.24, 95% CI: 0.15-0.38, p-value < 0.01), 5 hours/day (OR = 0.26, 95% CI: 0.13-0.51, p-value < 0.01), and six or more hours/day (OR = 0.21, 95% CI: 0.11-0.43, p-value < 0.01) are also significantly associated with lower odds of adverse experiences, suggesting protective effects of extended daily internet use against adverse childhood experiences. This study underscores a significant prevalence of ACEs among adolescents in ethnic minority communities in Lang Son province, pointing to an urgent need for comprehensive strategies to address these challenges.